Scar the sky : a novel - Scott, J. Todd (Crooked Lane Books, 2025)
Lightning never strikes twice --until it does. A killer is hunting down survivors of lightning strikes in this dark and twisting thriller, perfect for fans of J. H. Markert and Richard Chizmar. Everything changed for Andi Ellis when she was struck by lightning and her heart stopped. Andi was resuscitated, but she was never the same--electronics strangely malfunction in her presence: clocks can't keep time; batteries swiftly die. And while many lightning strike victims are left with temporary "lightning tree" markings, on her they are permanent scars. Years later Andi, her eight-year-old daughter, and a fellow lightning strike survivor have fled Texas and Andi's dangerous ex to go off the grid in a strange and secluded desert community. Meanwhile, two private investigators pursue a US senator's missing daughter who they find too late. When searching for information on the strange lightning scars on the girl's body, they find themselves pulled into an FBI investigation--people who have been struck by lightning are being murdered. As the death toll mounts, the task force traces the killer farther west--closer and closer to Andi Ellis and her daughter, and the haven she's carefully created. Thriller and horror readers will be enthralled by the dark turns in Scar the Sky.